Skin Diseases in a Pediatric Hospital of Nepal - Roushan Jahan; Shreedhar Khanal; Shraddha Shrestha; Niraj Parajuli (Dermatology Research and Practice)
The skin diseases of pediatric population are varied which change according to age and season. There is a rarity of studies on pediatric skin conditions from Nepal. This observational study from the only tertiary care referral pediatric center of the country highlighted the burden of pediatric skin diseases in Nepalese population. All new cases of pediatric patients less than 14 years of age consulting the pediatric dermatological OPD of Kanti Children’s Hospital from January 2017 to December 2017 were included in this study. Demographic details of all the patients such as age and sex were recorded. The diagnosis was made clinically in most instances and appropriate laboratory and histopathological examination were performed wherever necessary. A total of 7683 pediatric patients were included in the study. Among these, there were 4574 (59.53%) males and 3109 (40.47%) females. The most common skin condition was infections among 2463 (32.12%) followed by eczematous conditions in 1711(22.27%) and hypersensitivity reactions in 1510 (19.65%). Infections were more common during the summer months. Overall, both infectious and noninfectious skin diseases were significantly more common during the warmer (summer and spring) months as compared to colder (autumn and winter) months (p<0.001). This study shows that the pediatric dermatoses are common in Nepalese population.